Pemahaman Psikologis Siswa melalui Pendekatan Humanis dan Konstruktif dalam Pencapaian Hasil Belajar PAI - Rozinah, Siti; Harun, Muhammad Saleh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2024)
This research aims to know how the model of constructivism learning and humanism approach may equip the learning psychology among the students at the puberty age. In which the involvement of students in learning could affect in learning outcomes. A part of it, how the understanding of students’ psychology will help teachers to adjust themselves. This research is a qualitative research with a description method, and this research took place at Smart Ekselensia Junior High School. Data collecting is conducted through observation, interview and documentation. Data validity conducts through triangulation whether technic or the resources. Data analysis is done by collecting data, data reduction, data presented, taking conclusion and verification. Research results show that (1) a model of constructivism learning and humanism approach increased the positive impact at puberty age, such as addressing students’ curiosity and their willingness to try something new. (2) By understanding students’ psychology, teacher may adjust themselves in learning process and also equip the learning outcomes cognitively, affectively and psychomotor.